The Social Responsibility of Omani Private Universities and its Role in Supporting Organizational Reputation: Dhofar University as a Model - Duraah, Omar Mohammed; Tijani, Mohamed Osman; Hinnawi, Susan Elias (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to identify the extent to which private educational institutions are concerned about their social responsibilities, and to study the role of social responsibility dimensions in enhancing the reputation of educational institutions. An analytical, descriptive approach was adopted in this study, where Dhofar University was selected as a case study to implement this study. The study comprises all faculty members of Dhofar University, and their number is 196 members. A simple random sample of (132) faculty members was selected. The questionnaires were distributed to them and 130 questions were retrieved. Multiple regression analysis was used to test the hypotheses. One of the most important findings of the study is that Dhofar university practices its social responsibility with high degree with a mean of (3.95), Regarding the practice of dimensions of social responsibility, the most practiced dimension, by the faculty members, was the economic dimension with a mean of (4.18), followed by the legal dimension with a mean of (4.08), then moral dimension with a mean of (3.95), and finally the human dimension with a mean of (3.78). The findings showed high interest of the administration of Dhofar University to improve the organizational reputation of the university as its mean reached (3.75). The findings also indicated that there are two dimensions of social responsibility (the human dimension, the economic dimension) have a significant positive effect on the organizational reputation of the educational institution, while the other two dimensions (legal dimension, moral dimension) have no significant effect on the organizational reputation of the educational institution. According to these results, a number of recommendations and suggestions were presented to stimulate the social responsibility of private universities and enhance their role in supporting the organizational reputation of the educational institution.
Keywords: social responsibility; organizational reputation; Dhofar University; Sultanate of Oman